Simple Visualized Detection Method of Virulence-Associated Genes of Vibrio cholerae by Loop-Mediated Isothermal Amplification - Xu, Mengjie; Fu, Huiyu; Chen, Dailing; Shao, Zehuai; Zhu, Jun; Alali, Walid Q.; Chen, Lanming (Frontiers in Microbiology, 2019)
Vibrio cholerae is a leading waterborne pathogenic bacterium worldwide. It can cause human cholera that is still pandemic in developing nations. Detection of V. cholerae contamination in drinking water and aquatic products is imperative for assuring food safety. In this study, a simple, sensitive, specific, and visualized method was developed based on loop-mediated isothermal amplification (LAMP) (designated sssvLAMP) to detect virulence-associated (ctxA, tcpA, hapA, mshA, pilA, and tlh) and species-specific (lolB) genes of V. cholerae. Three pairs of oligonucleotide primers (inner, outer and loop primers) were designed and or synthesized to target each of these genes. The optimal conditions of the sssvLAMP method was determined, and one-step sssvLAMP reaction was performed at 65°C for 40 min. Positive results were simply read by the naked eye via color change (from orange to light green) under the visible light, or by the production of green fluorescence under the UV light (260 nm). The sssvLAMP method was more efficient in detecting 6.50×101-6.45×104-fold low number of V. cholerae cells, and more sensitive in V. cholerae genomic DNA (1.36×10-2-4.42×10-6 ng/reaction) than polymerase chian reaction (PCR) method. Among 52 strains of V. cholerae and 50 strains of non-target species (e.g., other Vibrios and common pathogens) examined, the sensitivity and specificity of the sssvLAMP method were 100% for all the target genes. Similar high efficiency of the method was observed when tested with spiked samples of water and aquatic products, as well as human stool specimens. Water from various sources and commonly consumed fish samples were promptly screened by this simple and efficient visualized method and diversified variation in the occurrence of the target genes was observed. V. cholerae strains could be mostly detected by the presence of hapA and tlh alone or in combination with other genes, indicating a variable risk of potentially pathogenic non-O1/O139 strains in edible food products. This novel LAMP method can be a promising tool to address the increasing need of food safety control of aquatic products.